2020
DOI: 10.7150/jca.33488
|View full text |Cite
|
Sign up to set email alerts
|

High level of RNF187 contributes to the progression and drug resistance of osteosarcoma

Abstract: Objectives: Ring finger protein 187 (RNF187) was recently demonstrated to be up-regulation and function as a promoter in multiple cancers. However, the roles of RNF187 in osteosarcoma (OS) are unclear. Here, we tried to reveal the clinicopathological and biological roles of RNF187 in OS. Materials and Methods:We employed the quantitative real-time polymerase chain reaction (qRT-PCR) and immunohistochemistry (IHC) to determine the expression of RNF187 in OS tissues and cells. Migration and invasion capacities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…International Publisher mechanisms through individual diagnosis, such as gene sequencing and chemotherapeutic drug screening. Great progress has been reported that chromosome abnormality, tumor suppressor gene abnormality, transcription factor, growth factor, WWOX and miRNAs play important roles in the occurrence and development of OS [8][9][10][11][12][13][14][15][16]. However, the above research is still in its infancy in use, and there is no sufficient evidence to show that patients' benefit from it.…”
Section: Ivyspringmentioning
confidence: 99%
“…International Publisher mechanisms through individual diagnosis, such as gene sequencing and chemotherapeutic drug screening. Great progress has been reported that chromosome abnormality, tumor suppressor gene abnormality, transcription factor, growth factor, WWOX and miRNAs play important roles in the occurrence and development of OS [8][9][10][11][12][13][14][15][16]. However, the above research is still in its infancy in use, and there is no sufficient evidence to show that patients' benefit from it.…”
Section: Ivyspringmentioning
confidence: 99%
“…The role of RNF187 in different tumours remains controversial. While RNF187 exhibits tumour-suppressive activities in oesophageal squamous cell carcinoma [ 22 ] and triple-negative breast cancer, [ 19 ] ectopic RNF187 expression predicts a poor outcome and contributes to tumour progression in lung cancer, [ 16 ] hepatocellular carcinoma, [ 17 ] osteosarcoma [ 26 ] and ovarian carcinoma. [ 27 ] This discrepancy may be due to the differential substrates targeted by RNF187 in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…RING finger protein 187 (RNF187), also known as RACO-1, belongs to the RING domain-containing protein family. It functions as an E3 ligase to modulate various cellular processes involved in malignant neoplasms including lung cancer, [ 16 ] hepatocellular carcinoma, [ 17 ] osteosarcoma [ 18 ] and breast cancer. [ 19 ] RNF187 forms a homodimer in nuclear specifically interacting with c-Jun, which is required for c-Jun/activator protein 1 (AP-1)-activated gene transcription.…”
Section: Introductionmentioning
confidence: 99%
“…RNF187, a E3 ubiquitin ligase to enable ubiquitin-protein transferase activity, has been widely reported to be an oncogene in multiple cancer types. For example, Chen et al demonstrated overexpression of RNF187 induced cell EMT and apoptosis resistance in NSCLC [ 49 ]; Shi et al revealed high level of RNF187 contributed to progression and drug resistance of osteosarcoma [ 50 ]; Liu et al identified an essential oncogenic role of RNF187 in metastasis of hepatocellular carcinoma [ 51 ]. All these previous literatures strongly implied Circ_0000915 may play a pivotal role in IHs, which has driven us to make a further study in this work.…”
Section: Discussionmentioning
confidence: 99%